تحليل فروق أسئلة الامتحان النهائي بين الصّفّ المتميّز والصّفّ العادي في المدرسة المتوسّطة الحكوميّة ۳ ليما فولوه كوتا - Tari Meilani, Tari Meilani; Yelfi Dewi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The problem in this study is in thequestions of superior classes and regular classes in MTSN 3 Lima Puluh Kota which have not been analyzed for the 8th grade Arabic exam. Which question have a difference between superior classes and regular classes. The purpose of this study id to find out thedifference in the quality of questions for superior classes and regular classes in term of validity,reliability,level of difficulty, differentiation,and effectiveness of deceivers. The research methodology used quantitative descriptive. The research instrument used are observation and documentation. The researcher used a Microsoft Excel program to conduct data analysis. The results of the research found by the researcher are that there are 22 valid questions and 18 invalid questions in the superior class exam questions, the superior class exam questions have a high level of reliability, and for the level of difficulty, there are 18 questions with the easy category, 21 questions with the medium category and 1 questions including the diffult is in the good category, and the level of effectiveness of the deceptions is declared to be functional. While in the regular class exam questions there are 30 valid questions and 10 invalid questions, the regular class exam questions have a high level of reliability, have 28 questions that are in the easy category,8 questions in the ,edium category and 4 questions in the difficult category. It has a good differentiation and the effectiveness of the deceptor is stated to be fuctional.